PELATIHAN DESIGN UI/UX PADA SISWA SMAN 58 JAKARTA - Nur Hayati; Fauziah Fauziah; Ira Diana Sholihati (LPPM Universitas Bina Bangsa, 2023)
Based on the results of an analysis of the Community Service training in the previous odd semester of 2022/2023 which made websites using wireframes, this time we are trying to improve the website creation training process by introducing User Interface (UI) and User Experience (UX) training first to the students of SMAN 58 Jakarta by using the figma application. This is intended to make the website design more attractive. Even though in the previous website creation training, students were able to create their own website design, the appearance of the design still looked stiff because they were still focused on how to make the website, not on website design. In fact, the basis of making the website itself lies in the appearance design of the website. The figma application was chosen because it is easy to use, is a sharing application so that website creation can be done together on the same file, has many features, is cloud-based so it doesn't require installation, there are lots of additional plugins and it's free. This Community Service was carried hybrid in the Computer Laboratory of SMAN 58 Jakarta on Friday Juni, 9 2023 at 9am-11.30am with 12 participants who had previously been selected from the school. Based on the survey results, 92% of participants answered that they had never used the figma application and 100% of participants thought that the figma application helped make website creation easier.